2010
DOI: 10.1080/13575271003789356
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Crisis Intervention Services for Youth within an Emergency Department: A View from Within

Abstract: An innovative crisis intervention program was created at the Children's Hospital of Eastern Ontario in Canada in order to provide emergency assessments for youth presenting with mental health crises. The current investigation presents an overview of the program and examined the emergency staff's perception and satisfaction with it. Eighty-seven emergency department medical staff completed a survey. Overall, emergency department staff place high value on having access to emergency mental health services, are pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(70 citation statements)
references
References 40 publications
2
67
0
1
Order By: Relevance
“…Many of the current program evaluations focus on assessing staff or professional perspectives (Dion et al, 2010;Krupa et al, 2010). Although program staff and other professionals offer an important viewpoint, clients can provide a unique outlook because they are the individuals with lived experiences and are immersed in the program.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many of the current program evaluations focus on assessing staff or professional perspectives (Dion et al, 2010;Krupa et al, 2010). Although program staff and other professionals offer an important viewpoint, clients can provide a unique outlook because they are the individuals with lived experiences and are immersed in the program.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a circle of care can provide support and alternative resources to access when attempting to resolve future crises. As well, the research literature on crisis intervention programs has also found that connecting service users to external agencies and professionals (Dion et al, 2010;Krupa et al, 2010;Malla, Norman, McLean, Scholten, & Townsend, 2003;Vingilis et al, 2007), can support the attainment of independent community living, as depicted in the Outcome component of the conceptual model.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Plusieurs rapports et articles déplorent un manque de services pour venir en aide à cette tranche de la population (Reid et Brown, 2008;CEPSM, 2010;Dion, et collab., 2010). En ce qui concerne les jeunes francophones ayant des problèmes de santé mentale, la situation se présente de façon encore plus complexe.…”
Section: Resultsunclassified
“…In practice, although there is some consensus about the merits of crisis intervention services, the research is again fragmented and based on the experiences of adults. Crisis intervention services are considered to be least intrusive, provide effective support for both the person and family, as well as divert people away from emergency room visits, involvement with police, and/or costly out-of-home placements (Dion, Kennedy, Cloutier, & Gray, 2010;Doulas & Lurigio, 2010;Ruffin, Spencer, Abel, Gage, & Miles, 1993;Shulman & Athey, 1993). Moreover, there are significant concerns about the lack of coordination between systems, such as the child and youth mental health and police systems (Doulas & Lurigio, 2010;Duvall, Young, & KaysBurden, 2012).…”
Section: Social Work Practice In Child and Youth Mental Healthmentioning
confidence: 98%